3D numerical simulations of a LOVA reproduction inside the new facility STARDUST-UPGRADE. (1st February 2017) - Ciparisse, J.F.; Malizia, A.; Poggi, L.A.; Tieri, F.; Gelfusa, M.; Murari, A.; Papa, C. Del; Giovannangeli, I.; Gaudio, P.
Abstract: A loss of vacuum in a vessel, containing or not dust, is the typical case study considered in the STARDUST-UPGRADE facility of the Quantum Electronics and Plasma Group of the university of Rome Tor Vergata. This kind of accident was simulated numerically, without including the presence of dust, for two mass flow rates and three different inlet ports (C, E and F). Numerical settings are explained and the results obtained in each case are shown and discussed. At the end of the work, conclusions about what seen and further foreseen developments of this research are presented.